2007
DOI: 10.1128/jcm.00458-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hand-Held Test Kits, Immunofluorescence Microscopy, Enzyme-Linked Immunosorbent Assay, and Flow Cytometric Analysis for Rapid Presumptive Identification of Yersinia pestis

Abstract: An in-house immunochromatographic test, Plague BioThreat Alert test strips, ABICAP columns, enzymelinked immunosorbent assay, flow cytometry, and immunofluorescence microscopy were compared for the detection of the fraction 1 capsular antigen of Yersinia pestis, using spiked buffer and clinical specimens. Hand-held test kits proved to be excellent benchtop tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 10 publications
1
37
0
1
Order By: Relevance
“…Commercially available diagnostics such as the Plague BioThreat Alert test strips are based on the detection of the fraction 1 capsular antigen. The sensitivity limits of detection are between 6 ϫ 10 3 and 7 ϫ 10 3 CFU/ml, which is similar to the detection sensitivity described in this report (33). However, both of these sensitivity limits pale in comparison with that of real-time PCR, which can detect between 0.01 and 1 pg of extracted DNA; assuming a 100% extraction efficiency, this translates to approximately 1 CFU (24,32).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Commercially available diagnostics such as the Plague BioThreat Alert test strips are based on the detection of the fraction 1 capsular antigen. The sensitivity limits of detection are between 6 ϫ 10 3 and 7 ϫ 10 3 CFU/ml, which is similar to the detection sensitivity described in this report (33). However, both of these sensitivity limits pale in comparison with that of real-time PCR, which can detect between 0.01 and 1 pg of extracted DNA; assuming a 100% extraction efficiency, this translates to approximately 1 CFU (24,32).…”
Section: Discussionsupporting
confidence: 51%
“…Y. pestis A1122 is an exempt select-agent strain (26) which lacks the pgm locus and the pCD1 plasmid, both of which encode critical virulence factors. Attenuated strains are commonly used for research purposes in order to demonstrate diagnostic detection feasibility (21,31,33). Although we used an attenuated strain in this study, there is strong evidence to indicate that the results obtained will translate to fully virulent Y. pestis strains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the F1 antigen could be detected at a concentration of 0.5 ng/ml, while 3 ϫ 10 3 CFU/ml of plague bacilli gave a positive reaction (9,10,13,46). Specifically, a recent study with the same Plague BioThreat Alert test strips from Tetracore reported a detection limit of 37 ng/ml for the purified F1 antigen and 6 ϫ 10 3 CFU/ml for the bacteria (46).…”
Section: Vol 49 2011 Rapid Identification Of Capsular Y Pestis Strmentioning
confidence: 99%
“…Our studies are the first to use these kits with a highly virulent CO92 Y. pestis strain and its authentic F1 mutant. The presence of the F1 antigen in plague patient sera has been reported in several studies and ranged from as low as 4 ng/ml to as high as 50,000 ng/ml (8,46,51). However, antigenemia was not present in all patients with acute plague, and only 20% of their sera were positive for the Fl antigen (51).…”
Section: Vol 49 2011 Rapid Identification Of Capsular Y Pestis Strmentioning
confidence: 99%
“…BioThreat Alert Ò Assays have previously been evaluated for the detection of other biothreat agents, including orthopoxviruses, 50 ricin, 33 abrin, 34 and Yersinia pestis. 51 Limited evaluations have also been conducted with LFAs for the detection of Francisella tularensis (unpublished data), botulinum neurotoxins, 52 and staphylococcal enterotoxins. 53 In an earlier study, King et al 54 detected 10 5 spores/mL of B. anthracis Pasteur strain using the Tetracore BTA LFA.…”
Section: Discussionmentioning
confidence: 99%